Answer:
Step-by-step explanation: Simplifying
2(3y + -5) + -2 = 3(y + -3)
Reorder the terms:
2(-5 + 3y) + -2 = 3(y + -3)
(-5 * 2 + 3y * 2) + -2 = 3(y + -3)
(-10 + 6y) + -2 = 3(y + -3)
Reorder the terms:
-10 + -2 + 6y = 3(y + -3)
Combine like terms: -10 + -2 = -12
-12 + 6y = 3(y + -3)
Reorder the terms:
-12 + 6y = 3(-3 + y)
-12 + 6y = (-3 * 3 + y * 3)
-12 + 6y = (-9 + 3y)
Solving
-12 + 6y = -9 + 3y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-3y' to each side of the equation.
-12 + 6y + -3y = -9 + 3y + -3y
Combine like terms: 6y + -3y = 3y
-12 + 3y = -9 + 3y + -3y
Combine like terms: 3y + -3y = 0
-12 + 3y = -9 + 0
-12 + 3y = -9
Add '12' to each side of the equation.
-12 + 12 + 3y = -9 + 12
Combine like terms: -12 + 12 = 0
0 + 3y = -9 + 12
3y = -9 + 12
Combine like terms: -9 + 12 = 3
3y = 3
Divide each side by '3'.
y = 1
Simplifying
y = 1